2012
DOI: 10.5354/0717-3652.2012.20296
|View full text |Cite
|
Sign up to set email alerts
|

Diseño y evaluación de proceso de una intervención comunitaria para la detección precoz del primer episodio de psicosis en Chile

Abstract: Diseño y evaluación de proceso de una intervención comunitaria para la detección precoz del primer episodio de psicosis en Chile Introducción: La esquizofrenia es una enfermedad mental que genera discapacidad, afectando la calidad de vida de la persona y de sus cuidadores. Las investigaciones demuestran que un menor tiempo de psicosis no tratada durante el primer episodio se asocia con un mejor pronóstico. Objetivo: En este trabajo se describe el diseño y evaluación de proceso de una intervención comunitaria p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The studies described seven EIP programmes (some articles referred to the same programme) and were conducted in Argentina, Brazil, Chile and Mexico. The study designs consisted of two randomized‐controlled trials (RCTs) (Valencia, Juarez, Delgado, Díaz, et al, 2017; Valencia, Juarez, & Ortega, 2012), six observational studies (Cabral & Chaves, 2010; Chaves, 2007; Gaspar et al, 2019; Gonzalez‐Valderrama et al, 2017; Louzã, Azevedo, Macedo, & Gattaz, 2008; Padilla et al, 2015) and two qualitative analyses (Eisenstadt, Monteiro, Diniz, & Chaves, 2012; Valenzuela, Pastorino, Alvarado, Villalón, & Vanegas, 2012). Sample sizes ranged from 16 to 102 participants with a mean (SD) of 33.7 (34.1) participants.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies described seven EIP programmes (some articles referred to the same programme) and were conducted in Argentina, Brazil, Chile and Mexico. The study designs consisted of two randomized‐controlled trials (RCTs) (Valencia, Juarez, Delgado, Díaz, et al, 2017; Valencia, Juarez, & Ortega, 2012), six observational studies (Cabral & Chaves, 2010; Chaves, 2007; Gaspar et al, 2019; Gonzalez‐Valderrama et al, 2017; Louzã, Azevedo, Macedo, & Gattaz, 2008; Padilla et al, 2015) and two qualitative analyses (Eisenstadt, Monteiro, Diniz, & Chaves, 2012; Valenzuela, Pastorino, Alvarado, Villalón, & Vanegas, 2012). Sample sizes ranged from 16 to 102 participants with a mean (SD) of 33.7 (34.1) participants.…”
Section: Resultsmentioning
confidence: 99%
“…Sample sizes ranged from 16 to 102 participants with a mean (SD) of 33.7 (34.1) participants. Most of the studies were conducted in specialized settings, mainly research centres or tertiary care, with only two studies carried out in primary care (Padilla et al, 2015; Valenzuela et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specialized training sessions for health teams should be established, since several studies have shown that their detection capability can be very low, as observed in a southern region of Chile, where only 1 in every 20 individuals with depression were correctly diagnosed in primary care centers (Alvarado et al 2006b). In the case of individuals with first episode psychosis, we have found that the detection rate in primary care centers is close to a third of all cases and that this rate is significantly improved after a brief training of professional and technical teams (Alvarado et al 2014;Valenzuela et al 2012).…”
Section: Challenges Facing Mental Health Services In Santiagomentioning
confidence: 99%